The Influence of Listening English Song to Improve Listening Skill in Listening Class - Tri Listiyaningsih (Academica: Journal of Multidisciplinary Studies, 2017)
This article is written to describe the influence of listening English song to improve listening skill, especially in the listening class. What influence that embossed by listening English song also will explain in this article. Through the qualitative method, the data gathered showed that listening English song can improve listening skill. Listening skill is one of skill in the English language that should be mastered. People who learn the English language should master the listening skill. To improve listening skill, people can exercise through listening English song because listening English song has the benefit to improve listening skill.Keywords:Listening, English-song, Improve, Listening-skill.